Discovery and Genetic Validation of Chemotherapeutic Targets for Chagas' Disease - Osorio-Méndez, Juan Felipe; Cevallos, Ana María (Frontiers in Cellular and Infection Microbiology, 2019)
There is an urgent need to develop new treatments for Chagas´ disease. To identify drug targets, it is important to understand the basic biology of Trypanosoma cruzi, in particular with respect to the biological pathways or proteins that are essential for its survival within the host. This review provides a streamlined approach for identifying drug targets using freely available chemogenetic databases and outlines the relevant characteristics of an ideal chemotherapeutic target. Among those are their essentiality, druggability, availability of structural information, and selectivity. At the moment only 16 genes have been found as essential by gene disruption in T. cruzi. At the TDR Targets database, a chemogenomics resource for neglected diseases, information about published structures for these genes was only found for three of these genes and annotation of validated inhibitors was found in two. These inhibitors have activity against the parasitic stages present in the host. We then analyzed three of the pathways that are considered promising in the search for new targets: 1. Ergosterol biosynthesis, 2. Resistance to oxidative stress, 3. Synthesis of surface glycoconjugates. We have annotated all the genes that participate in them, identified those that are considered as druggable, and incorporated evidence from either Trypanosoma brucei, and Leishmania spp. that supports the hypothesis that these pathways are essential for T. cruzi survival.